Carbon, oxygen, and strontium isotope geochemistry of the Proterozoic carbonate rocks, Bhima basin, south India: Implication for diagenesis - Nagarajan, Ramasamy; Armstrong-Altrin, John; Sial, Alcides; Nagendra, Raghavendra; Ellam, Rob (Universitatea de Nord din Baia Mare, 2013)
A carbonate dominated shallow marine Proterozoic Bhima basin consists of carbonates and clastic rocks, and is widely distributed in the northern part of the Karnataka state, south India. Limestones of the Shahabad Formation have been selected for this study and secular variations in C, O, and Sr isotope compositions are reported. δ13C values are varying from +3.50 to -1.38‰PDB. Similarly, the δ18O values recorded a range between -5.76 and -12.93‰PDB 87Sr/86Sr ratio for these limestones is varying between 0.70699 and 0.7117. Higher burial rate of organic matter could have been responsible for the positive δ13C values, which is common in the Proterozoic carbonate rocks. The δ18O values in most of the samples are similar to the average value of the Proterozoic carbonate rocks. Albeit some of the samples are modified in their original isotopic signature, which shows high negative δ18O values < -10‰PDB, Mn/Sr ratios > 1.5 and a negative trend between δ18O and 87Sr/86Sr, suggesting that the δ18O and 87Sr/86Sr isotopic signatures of Bhima carbonates have been altered by diagenesis. The post depositional diagenetic alteration is also supported by the petrographic characters of these carbonates.